Application of a Stochastic Multicriteria Acceptability Analysis to support decision-making within a macro-scale energy model: Case study of the electrification of the road European transport sector. (1st December 2021) - Lerede, Daniele; Pinto, Giuseppe; Saccone, Mirko; Bustreo, Chiara; Capozzoli, Alfonso; Savoldi, Laura
Abstract: Energy system models based on the TIMES framework can explore possible energy futures through the construction of a network of technological processes, to satisfy a set of exogenously imposed service demands at the least-cost system configuration. This work presents a methodology aimed at supporting decision-makers in finding optimal energy-system configuration in a complex energy environment, characterized by uncertain information. First, the EUROfusion TIMES Model is used to assess the sensitivity of different long-term evolutions of the European energy system, with particular reference to the road transport sector, considering different trends for the prescribed future variations of investment cost and vehicle efficiency. In a second step, the Stochastic Multicriteria Acceptability Analysis is used to critically evaluate the alternative optimal configurations proposed by the model simulations under a set of economic and environmental criteria. The results of the analysis allow the discussion of the influence of such criteria on the different alternative cases, complementing the cost minimization approach. In the case study considered here, high penetrations of electric vehicles in the road fleet are favored by economic, environmental and energy-related priorities. Highlights: Uncertainty assessment in optimization macro-scale energy system models addressed. Different alternative electric vehicle fleets analyzed with EUROfusion TIMES Model. Multicriteria Decision Analysis applied to complement minimum-cost optimization. 4 preference criteria analyzed by Stochastic Multicriteria Acceptability Analysis. The alternatives can be ranked according to preference criteria and weights.